Crystal structure of 2-[(4-bromobenzyl)thio]-5-(5-bromothiophen-2-yl)-1,3,4-oxadiazole, C13H8Br2N2OS2 - Al-Omary Fatmah A. M.; Blacque Olivier; Alanazi Fahdah S.; Tiekink Edward R. T.; El-Emam Ali A. (Zeitschrift für Kristallographie - New Crystal Structures)
C13H8Br2N2OS2, monoclinic, Pc (no. 7), a = 13.4050(4) Å, b = 4.7716(1) Å, c = 11.7303(4) Å, β = 105.885(3)∘$105.885{(3)}^{° }$, V = 721.66(4) Å3, Z = 2, Rgt${R}_{gt}$(F) = 0.0294, wRref$wR_{ref}$(F2 = 0.0808, T = 160 K.